The uncertainty of the BSRN monthly mean Global 1 and Global 2 fluxes due to missing hourly means with and without quality-control and an examination through validation of the NASA GEWEX SRB datasets. (November 2020) - Zhang, Taiping; Stackhouse, Paul W.; Cox, Stephen J.; Mikovitz, J. Colleen
Highlights: Derived uncertainties of BSRN Global 1 and Global 2 monthly means due to missing hourly means using Monte Carlo method. Compared BSRN Global 1 and Global 2 with and without quality-check. Quality-check affects Global 1 less than Global 2. Quality-checked monthly mean Global 1 and Global 2 on average differ by less than 1 W m −2 . Preliminary GEWEX SRB GSW(V4.0-IP) agree best with quality-checked Global 1. Abstract: The Baseline Surface Radiation Network (BSRN) is a project of the Data and Assessments Panel from the Global Energy and Water Exchanges (GEWEX) under the umbrella of the World Climate Research Programme (WCRP). Currently in the archive there are data from 67 sites located in all seven continents spanning from 1992 to the present. The original BSRN records are at 1-, 2-, 3- or 5-minute intervals, and sophisticated quality-control procedures have been developed to eliminate erroneous records before hourly, daily and monthly means are computed. The resulting gaps from quality-control, however, give rise to uncertainties in computed temporal averages on various scales. There are two types of total shortwave downward fluxes: The Global 1 which is the sum of direct horizontal and diffuse irradiances, observed using the pyrheliometer and radiometer, respectively, and is recommended by the BSRN committee for its higher precision, and the Global 2 which is observed using the pyranometer. It has been found that, compared to Global 2, Global 1 is more susceptible to errors, thus resulting in more gaps in the original records. Here we examine the effect of quality-control on the monthly mean Global 1 and Global 2 and attempt to quantify the resulting uncertainties through analysis of the quality-control procedure and averaging algorithm and comparison with the NASA GEWEX Surface Radiation Budget (SRB) dataset. The SRB project is now making progress toward its Release 4.0 Integrated Products (Rel. 4.0-IP or V4.0-IP) with changes in both algorithm and inputs on the basis of its Release 3.0 (Rel. 3.0 or V3.0) products. The preliminary results from Rel. 4.0-IP span 34 years continuously from July 1983 to June 2017 on a 1° by 1° quasi-equal-area grid system in the form of 3-hourly, daily and monthly means. It is found that Global 2 generally has fewer missing records and is less affected by the quality-check procedure; on average, the monthly mean Global 1 and Global 2 differ by less than 1 W m −2 ; the GEWEX SRB preliminary GSW(V4.0-IP) monthly mean shortwave downward fluxes agree the best with the BSRN Global 1 monthly means computed from observational records that are nearly complete and that survive the quality-check nearly completely.